High PEEP in ARDS: quantitative evaluation between improved oxygenation and decreased oxygen delivery - Chikhani, M.; Das, A.; Haque, Mainul; Wang, W.; Bates, D.G.; Hardman, J.G. (Oxford University Press, 2016)
Background: Positive end-expiratory pressure (PEEP) is widely used to improve oxygenation and prevent alveolar collapse in mechanically ventilated patients with the acute respiratory distress syndrome (ARDS). While PEEP predictably improves arterial oxygenation, high PEEP strategies have demonstrated equivocal improvements in ARDS mortality. The effect of PEEP on tissue oxygen delivery is poorly understood and is difficult to quantify or investigate in the clinical environment. Methods: We investigated the effects of PEEP on tissue oxygen delivery in ARDS using a novel, high-fidelity, computational model with highly integrated respiratory and cardiovascular systems. The model was configured to replicate published clinical trial data on the responses of individual ARDS patients to changes in PEEP. These virtual patients were subjected to increasing PEEP levels during a lung-protective ventilation strategy (0 - 20 cmH2O). Measured variables included arterial oxygenation, cardiac output, peripheral oxygen delivery and alveolar strain. Results: As PEEP increased, tissue oxygen delivery decreased in all subjects (mean reduction 25% at 20 cmH2O PEEP), despite an increase in arterial oxygen tension (mean increase 6.7 kPa, at 20 cmH2O PEEP). Changes in arterial oxygenation and tissue oxygen delivery differed between subjects, but showed a consistent pattern. Static and dynamic alveolar strain decreased in all patients as PEEP increased. Conclusions: Incremental PEEP in ARDS appears to protect alveoli and improve arterial oxygenation, but also appears to significantly impair tissue oxygen delivery due to reduced cardiac output. We propose why this trade-off may explain the poor improvements in mortality associated with high PEEP ventilation strategies.